2015
DOI: 10.1161/circgenetics.114.000635
|View full text |Cite
|
Sign up to set email alerts
|

Pro12Ala Polymorphism of the PPARγ2 Gene Interacts With a Mediterranean Diet to Prevent Telomere Shortening in the PREDIMED-NAVARRA Randomized Trial

Abstract: Background— The gene variant Pro/Ala (rs1801282) in the PPARγ2 has been associated with lower cardiovascular risk and greater benefit from lifestyle interventions. This polymorphism also seems to be associated with longer lifespan, but no information on telomere length (TL) is available. Our aim was to study the association between the Ala allele and changes in TL in high cardiovascular risk subjects and the potential interaction with a Mediterranean dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 47 publications
1
42
1
Order By: Relevance
“…In this study participants who were given the MD supplemented with olive oil showed no differences in telomere erosion over a five year period when compared to a control group given a low fat diet; unexpectedly, accelerated telomere shortening was observed in participants on the MD supplemented with nuts [75]. Importantly however, the study found that greater adherence to the MD reduced telomere shortening in individuals carrying the Ala variant of the PPARγ2 gene, but not in those carrying the Pro variant [74]. Thus, although the study concluded that overall there was no beneficial effect of the MD intervention on slowing telomere shortening in comparison to a low fat diet, it also highlighted the potential relevance of genetic factors when considering the effects of diets on telomere length.…”
Section: Dietary Interventionscontrasting
confidence: 55%
See 1 more Smart Citation
“…In this study participants who were given the MD supplemented with olive oil showed no differences in telomere erosion over a five year period when compared to a control group given a low fat diet; unexpectedly, accelerated telomere shortening was observed in participants on the MD supplemented with nuts [75]. Importantly however, the study found that greater adherence to the MD reduced telomere shortening in individuals carrying the Ala variant of the PPARγ2 gene, but not in those carrying the Pro variant [74]. Thus, although the study concluded that overall there was no beneficial effect of the MD intervention on slowing telomere shortening in comparison to a low fat diet, it also highlighted the potential relevance of genetic factors when considering the effects of diets on telomere length.…”
Section: Dietary Interventionscontrasting
confidence: 55%
“…The studies were generally small and heterogeneous with respect to the age and health characteristics of the participants, as well as the duration of the interventions. The majority lasted for less than a year [62][63][64][65][66][67][68][69][70][71][72], while four trials were conducted for a year or more [73][74][75][76][77]. In all of them telomere length was determined in either leukocytes or PBMC before and after the intervention.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…The T/S ratio was calculated as follows [2 CT(telomeres) /2 CT(single copy gene) ] =2 ‐ΔCT , because the amount of the PCR product approximately doubles in each cycle of the PCR . More detailed information about this method has been published elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The T/S ratio was calculated as follows [2 CT(telomeres) /2 CT(single copy gene) ] =2 -ΔCT , because the amount of the PCR product approximately doubles in each cycle of the PCR (21). More detailed information about this method has been published elsewhere (2,3,22) For quality control, all samples were run in triplicate and checked for concordance between triplicate values. In order to achieve a robust consistence, samples showing a high variation (more than 10%) were rerun and reanalysed.…”
Section: Telomere Length Assessmentmentioning
confidence: 99%
“…[1113], and lower rates of telomere shortening compared with the Pro/Pro genotype. [14] Results from studies investigating the association between the Pro 12 Ala polymorphism and breast-cancer risk have been conflicting: some studies reported a marginally increased risk associated with the Ala genotype. [15,16], although others did not.…”
Section: Introductionmentioning
confidence: 99%